2014
DOI: 10.1136/oemed-2014-102429
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime shift work exposure: association with anthropometry, body composition, blood pressure, glucose and heart rate variability

Abstract: The association of lifetime shift work exposure with PC2 and PC3 suggests that shift work promotes unfavourable changes in autonomic cardiac control related to a decrease in parasympathetic modulation and an increase in blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 58 publications
1
14
0
3
Order By: Relevance
“…This is also consistent with the previous studies in non-firefighter working populations (Hayashi et al 1996; Kubo et al 2013; Nakamura et al 2012; Ohira et al 2000; Souza et al 2015; Su et al 2008; Suwazono et al 2008). However, this study is very unique in demonstrating that long work hours/overtime is an independent significant risk factor among 24-h shift workers, after adjustment for multiple other occupational risk factors (job strain, effort–reward imbalance, and physical demands), which has been unclear (Gilbert-Ouimet et al 2014; Peter et al 1999; Virkkunen et al 2007).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is also consistent with the previous studies in non-firefighter working populations (Hayashi et al 1996; Kubo et al 2013; Nakamura et al 2012; Ohira et al 2000; Souza et al 2015; Su et al 2008; Suwazono et al 2008). However, this study is very unique in demonstrating that long work hours/overtime is an independent significant risk factor among 24-h shift workers, after adjustment for multiple other occupational risk factors (job strain, effort–reward imbalance, and physical demands), which has been unclear (Gilbert-Ouimet et al 2014; Peter et al 1999; Virkkunen et al 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, despite some evidence for shift work or overtime work as a risk factor for clinically assessed high blood pressure or hypertension in non-firefighter working populations (Hayashi et al 1996; Kubo et al 2013; Nakamura et al 2012; Ohlander et al 2015; Ohira et al 2000; Sakata et al 2003; Souza et al 2015; Su et al 2008; Suwazono et al 2008), none of the studies examined the impact of the unique shift schedules of most US professional firefighters who work a 24-h shift work schedule, including frequent additional/overtime 24-h shifts (Choi et al 2014b). Also, most of the studies have considered only shift work or overtime as the occupational risk factor in analyses.…”
Section: Introductionmentioning
confidence: 99%
“…This risk is increased in those who work night shifts for many years, including visceral fat area. 3, 37, 38, 39 Night workers have higher risk to develop diabetes, and in a study with women working night shifts, they showed increased risk to develop type 2 diabetes in 3 years, and the risk gets higher as the working years extend. 40, 41 …”
Section: Discussionmentioning
confidence: 99%
“…Although work-stress was not specifically addressed in the present study, we adjusted for influence at work (decision authority), which is a psychosocial factor of importance for inactive behavior [ 51 ]. Also, by performing a secondary analysis with exclusion of workers reporting night-shift work, we accounted (at least to some extent) for potential confounding by the occurrence of general fatigue due to irregular work hours [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%